PENGARUH PEMBELAJARAN SAVI TERHADAP HASIL BELAJAR MATERI TERMOKIMIA SMAN 1 TELUK KUANTAN - Artika Artika; Asregi Asril; Nofri Yuhelman (Universitas Islam Kuantan Singingi, 2020)
This study aims to determine student learning outcomes in Thermochemical material in class XIMIPA SMA Negeri 1 Teluk Kuantan. This research was a quantitative research type of quasiexperimentaldesign with posttest-only control design experimental design. The sample in this study were students of class XI MIPA 1 as an experimental class and class XI MIPA 2 as a control class. The sampling technique was cluster random sampling. This study used theKolmogorov-smirnov test. In this study using the